The Use of Raw Poultry Waste as Soil Amendment Under Field Conditions Caused a Loss of Bacterial Genetic Diversity Together with an Increment of Eutrophic Risk and Phytotoxic Effects - Pin Viso, Natalia Daniela (2022)
Poultry waste has been used as fertilizer to avoid soil degradation caused by the long-term application of chemical fertilizer. However, few studies have evaluated field conditions where livestock wastes have been used for extended periods of time. In this study, physicochemical parameters, metabarcoding of the 16S rRNA gene, and ecotoxicity indexes were used for the characterization of chicken manure and poultry litter to examine the effect of their application to agricultural soils for 10 years. Poultry wastes showed high concentrations of nutrients and increased electrical conductivity leading to phytotoxic effects on seeds. The bacterial communities were dominated by typical members of the gastrointestinal tract, noting the presence of pathogenic bacteria. Soils subjected to poultry manure applications showed statistically higher values of total and extractable phosphorous, increasing the risk of eutrophication. Moreover, while the soil bacterial community remained dominated by the ones related to the biogeochemical cycles of nutrients and plant growth promotion, losses of alpha diversity were observed on treated soils. Altogether, our work would contribute to understand the effects of common local agricultural practices and support the adoption of the waste treatment process in compliance with environmental sustainability guidelines.